2017
DOI: 10.1038/bjc.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vitamin D pathway genetic variation and circulating 25-hydroxyvitamin D on cancer outcome: systematic review and meta-analysis

Abstract: Background:Vitamin D has been linked with improved cancer outcome. This systematic review and meta-analysis investigates the relationship between cancer outcomes and both vitamin D-related genetic variation and circulating 25-hydroxyvitamin D (25OHD) concentration.Methods:A systematic review and meta-analysis of papers until November 2016 on PubMed, EMBASE and Web of Science pertaining to association between circulating vitamin D level, functionally relevant vitamin D receptor genetic variants and variants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 122 publications
6
120
0
3
Order By: Relevance
“…The results of these studies also suggest that studying VDR polymorphisms in order to strengthen our understanding of the vitamin D pathway could provide additional evidence for its protective therapeutic role against cancer development (33,79). VDR polymorphisms might also serve as indicators for diagnosis, occurrence, and prognosis as well as survival in cancer (24,64,(75)(76)(77)(78)(83)(84)(85). There have been many epidemiological studies of breast, prostate and colorectal cancer, however, there are limited reports on the association of VDR polymorphism with lung, thyroid, oesophageal, ovarian, renal and hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of these studies also suggest that studying VDR polymorphisms in order to strengthen our understanding of the vitamin D pathway could provide additional evidence for its protective therapeutic role against cancer development (33,79). VDR polymorphisms might also serve as indicators for diagnosis, occurrence, and prognosis as well as survival in cancer (24,64,(75)(76)(77)(78)(83)(84)(85). There have been many epidemiological studies of breast, prostate and colorectal cancer, however, there are limited reports on the association of VDR polymorphism with lung, thyroid, oesophageal, ovarian, renal and hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 97%
“…A recent meta-analysis found a clear and strong association between low levels of baseline vitamin D and poorer survival and an association between VDR genetic variants and survival [rs7975232 (ApaI) with progression-free survival; rs1544410 (BsmI) with overall survival; and rs2228570 (FokI) with overall survival] in lung cancer. However, from all the observational studies included in this meta-analysis, a causal relationship was not conclusively established (85).…”
Section: Additional Cancer-related Interactions Of Vdr Polymorphismsmentioning
confidence: 92%
“…It has been reported that SNPs in the VDR gene are associated with tumorigenesis in various organs such as prostate [12], breast [13], skin [14], colon and rectum [15], and kidneys [16] but these observations are conflicting and debatable [17]. The interaction between VDR gene polymorphisms and vitamin D status has a pivotal role in cancer prognosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…(9) Consistent with this hypothesis, observational cohort studies have shown improved survival in cancer patients with higher circulating vitamin D concentrations, measured before or shortly after diagnosis of cancer. (10) However, evidence linking vitamin D status to organ-specific cancer survival is sparse and has produced conflicting results between and within types of cancers. (10)(11)(12) Specific to liver cancer, few studies have been conducted.…”
mentioning
confidence: 99%
“…(10) However, evidence linking vitamin D status to organ-specific cancer survival is sparse and has produced conflicting results between and within types of cancers. (10)(11)(12) Specific to liver cancer, few studies have been conducted. (12,13) The total 25-hydroxyvitamin D (25OHD) level in serum or plasma is used currently to assess vitamin D status in routine clinical practice.…”
mentioning
confidence: 99%